Evaluating the Economic Value of Above-Ground Biomass Carbon Stocks in the Urban Forests of Banda Aceh City - Dharma, Wira; Yasmin, Yekki; Ariqah, Nada; Harnelly, Essy; Rizki, Alia; Fitri, Lenni; Amirunnas , Amirunnas; Rauzana, Anita; Zakaria, Rahmad (Universitas Negeri Semarang, 2025)
Urban forests play a pivotal role in climate change mitigation by storing carbon in biomass. However, the economic valuation of this ecosystem service in Banda Aceh City remains underexplored. This study aims to quantify aboveground biomass carbon stocks and assess their economic value in six selected urban forests across the city. Non-destructive sampling was conducted using 20 × 20 m plots to measure tree diameter, estimate biomass using species-specific allometric equations, and calculate carbon content (C = 0.5 × B). A carbon price of US50/ton was applied for economic valuation. The total carbon stock was estimated at 11,579 tons, with Putroe Phang Forest contributing the highest proportion (45%). The corresponding economic value was approximately IDR 3.42 billion. A strong positive correlation (R² = 0.9859) was observed between tree diameter and biomass. This study presents a novel economic perspective on urban forest carbon in Banda Aceh by integrating ecological data with financial valuation. The findings underscore the importance of incorporating carbon trading mechanisms into urban planning to strengthen ecosystem service assessments and climate policy implementation.